Rescue and characterization of PCV4 infectious clones: pathogenesis and immune response in piglets - Chen, Lan; Deng, Li-Shuang; Xu, Tong; Lai, Si-Yuan; Ai, Yan-Ru; Zhu, Ling; Xu, Zhi-Wen (Frontiers in Microbiology, 2024)
Porcine circovirus 4 (PCV4) was first identified in 2019, categorized within the genus Circovirus in the family Circoviridae. To date, the virus has not been isolated from clinical samples. Meanwhile, many aspects of the biology and pathogenic mechanisms of PCV4 infection remain unknown. In this study, PCV4 was successfully rescued from an infectious clone. We utilized a PCV4 virus stock derived from this infectious clone to intranasally inoculate 4-week-old specific-pathogen-free piglets to evaluate PCV4 pathogenesis. The rescued PCV4 was capable of replicating in both PK-15 cells and piglets, with the virus detectable in nearly all collected samples from the challenge groups. Pathological lesions and PCV4-specific antigens were observed in various tissues and organs, including the lungs, kidneys, lymph nodes, spleen, and liver, in the inoculated piglets. Additionally, the levels of pro-inflammatory cytokines in the serum of the PCV4-inoculated group were significantly elevated compared to the control group, indicating that the induced inflammatory response may contribute to tissue damage associated with PCV4 infection. These findings offer new insights into the pathogenesis and inflammatory responses associated with PCV4-related diseases.